When All Else Fails: A Rare Case of Postoperative Toxic Shock Syndrome Arising from Surgical Site Infection after Decompressive Neurectomy Successfully Treated with Angiotensin-2. (10th February 2021) - Chandra, Raghav; Gold, Samuel; Kohler, Casey; Valladares, Jason; Hennessy, Sara A.; Bhat, Sneha G.
Abstract : Toxic shock syndrome is a serious complication of Streptococcus pyogenes or Staphylococcus aureus infections associated with very high morbidity and mortality. Postoperative toxic shock syndrome is an extremely rare phenomenon which manifests as fevers, diffuse rash, septic shock, and death. We present the first reported case of toxic shock syndrome associated with a surgical site infection from a decompressive neurectomy for refractory migraines in a 41-year-old female as well as the first use of angiotensin-2 vasopressor therapy to treat persistent septic shock from toxic shock syndrome refractory to conventional therapies.